2017
DOI: 10.1044/2017_jslhr-l-16-0222
|View full text |Cite
|
Sign up to set email alerts
|

Language Outcomes in Children Who Are Deaf and Hard of Hearing: The Role of Language Ability Before Hearing Aid Intervention

Abstract: https://doi.org/10.23641/asha.5538868.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A retrospective cohort analysis in Canada showed that there is a significant improvement in expressive communication in hearing-impaired children after the fitting of hearing aid. [ 11 ] Another study evaluates the improvement in deaf children's expressive and receptive language skills post-hearing aid fitting showed an inverse correlation with age of diagnosis. [ 12 ] Meaning early diagnosis and fitting of hearing aid is associated with better outcome and higher language skills.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort analysis in Canada showed that there is a significant improvement in expressive communication in hearing-impaired children after the fitting of hearing aid. [ 11 ] Another study evaluates the improvement in deaf children's expressive and receptive language skills post-hearing aid fitting showed an inverse correlation with age of diagnosis. [ 12 ] Meaning early diagnosis and fitting of hearing aid is associated with better outcome and higher language skills.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, research has found positive results in speech and language development from early intervention programs aimed at hearing-impaired infants when the intervention takes place from their first year of life. These surveys have confirmed the importance of fitting amplification to ensure audibility of speech sounds as one of the conditions required for speech development in hearing-impaired children (1)(2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 73%